Modulation of local Ca(2+) release sites by rapid fluid puffing in rat atrial myocytes - Woo, Sun-Hee (2006)
Atrial myocytes that lack t-tubules, appear to have two functionally separate sarcoplasmic Ca(2+) stores: a peripheral store associated with plasmalemmal L-type calcium channels and a central store with no apparent proximity to L-type calcium channels. Here we describe a set of calcium sparks and waves that are triggered by puffing of pressurized (200–400 mmH(2)O) bathing solutions onto resting isolated rat atrial myocytes. Puffing of pressurized (200 mmH(2)O) solutions, identical to those bathing the myocytes from distances of ~150 μm onto the surface of a single myocyte triggered or enhanced spontaneously occurring peripheral sparks by 5–6 fold and central Ca(2+) sparks by 2–3 fold, without altering the unitary spark properties.. Exposure to higher pressure flows (400 mmH(2)O) often triggered longitudinally spreading Ca(2+) waves. These results suggest that pressurized flows may directly modulate Ca(2+) signaling of atrial myocytes by activating the intracellular Ca(2+) release sites.